Examining conceptualizations of mobile journalism - Lee, Jia En (2024)
In today's digital era, mobile phones have become indispensable in people's lives, and journalists are increasingly integrating them into their workflows, giving rise to the phenomenon of mobile journalism (MOJO). While MOJO enables journalists to report news stories promptly with photos or videos captured directly from the scene, there are concerns among journalists about its potential to replace traditional newsrooms. Moreover, there is often confusion between mobile journalism and citizen journalism, both stemming from the widespread use of mobile phones. However, there remains a lack of in-depth exploration and conceptualization of mobile journalism, particularly in the context of Malaysia. Therefore, this qualitative study aims to delve into the concept of mobile journalism through interviews and focus group discussions, providing a comprehensive understanding of its implications for traditional newsrooms. By shedding light on current practices and perspectives, especially within the Malaysian media landscape, this study seeks to contribute valuable insights for future research and serve as a reference for traditional newsrooms looking to incorporate mobile journalism strategies into their workflows. The results of this research are crucial not just for journalists and media organizations, but also for outsiders seeking clarity on the distinction between mobile journalism and citizen journalism.